Abandoned agricultural lands as a source of arsenic in semi-arid regions: Influence on human exposure and health risk assessment in vulnerable rural areas. (December 2020) - Moreno-Rodríguez, V.; Del Rio-Salas, R.; Loredo-Portales, R.; Briseño-Beltrán, A.; Romo-Morales, D.; Zepeda, J.; Peña-Ortega, M.; Espinoza-Maldonado, I.G.; de la O-Villanueva, M.
Abstract: Intensive agriculture has led to a worldwide pollution problems that have negatively affected ecosystems and human health. To determine abandoned agricultural fields as a source of arsenic, and to assess potential human health risk of a vulnerable rural population in northwestern Mexico, As concentration was measured in agricultural top soils, unpaved street dust, house backyard soil, school playground soil and TSP. Average As concentration in resuspendible fraction (<20 μm) of soils from abandoned fields is 16.2 mg kg −1 . Average contents were found in unpaved streets (17.9 mg kg −1 ), house backyards (18.5 mg kg −1 ) and school playgrounds (18.2 mg kg −1 ). Relatively higher concentrations were found in dust deposited on school roofs (16.8 mg kg −1 ) and in TSP (10.7 mg kg −1 ). Enrichment factors suggest a moderately severe enrichment in agricultural soils while rural soils and dust suggest a moderate enrichment. Hazard index values suggest that non-carcinogenic health effect is unlikely to occur in children (<6 years old) and adults if exposed to soil and dust. Regarding carcinogenic risk, obtained values exceeded the acceptable threshold, indicating a considerable potential of incidence of carcinogenic effects in population. Spatial distribution of hazard index indicates that children exposed to conditions of social fragility and backwardness are more likely to develop adverse health effects. Data obtained indicate that abandoned agricultural fields act as a source of contaminants related to historic and intense activity, and dust as an important pathway for dispersion in semi-arid regions. This investigation indicates that more and detailed risk assessments are required, and to explore other As sources in the El Poblado Miguel Alemán. Highlights: Abandoned agricultural fields act as a potential source of As through resuspension processes. Health risk assessment of vulnerable rural population was performed if exposed to As in soil and dust. Higher HI and RISK values geographically correspond to conditions of social fragility and backwardness.